2017
DOI: 10.1080/16742834.2017.1301188
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aerosol effective radiative forcing and surface air temperature response over eastern China in CMIP5 models

Abstract: The effective radiative forcing (ERF) and associated surface air temperature change over eastern China are estimated using multi-model results from CMIP5 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…Yin et al: Links of climate variability in Arctic sea ice Hebei was significantly larger than that in other regions of China (Wang et al, 2006;Shi et al, 2015). Revealed by the datasets from Shangdianzi Station, the long-term trend of O 3 concentrations in North China indicated that the O 3 pollution underwent a significant increase in the period 2005-2015, with an average rate of 1.13±0.01 ppb yr −1 (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yin et al: Links of climate variability in Arctic sea ice Hebei was significantly larger than that in other regions of China (Wang et al, 2006;Shi et al, 2015). Revealed by the datasets from Shangdianzi Station, the long-term trend of O 3 concentrations in North China indicated that the O 3 pollution underwent a significant increase in the period 2005-2015, with an average rate of 1.13±0.01 ppb yr −1 (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, due to fast economic development, air pollution has been increasing in China (Chen, 2013;Watts et al, 2018). The major air pollution types in China are haze pollution (i.e., high-level fine particulate matter) in winter (Yin et al, 2015;Wang, 2018) and surface ozone (O 3 ) pollution in summer (Ma et al, 2016;Tang et al, 2018). Due to drastic air pollution control in China since 2013, haze pollution has been controlled in recent years (the environmental statistics unit of a statistics center in Peking University, 2018), appearing as a sharp decrease in fine particulate matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hebei was significantly larger than that in other regions of China (Wang et al, 2006;Shi et al, 2015). Revealed by the datasets from Shangdianzi Station, the long-term trend of O 3 concentrations in North China indicated that the O 3 pollution underwent a significant increase in the period 2005-2015, with an average rate of 1.13±0.01 ppb yr −1 (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Over the past several decades, due to fast economic development, air pollution has been increasing in China (Chen, 2013;Watts et al, 2018). The major air pollution types in China are haze pollution (i.e., high-level fine particulate matter) in winter (Yin et al, 2015;Wang, 2018) and surface ozone (O 3 ) pollution in summer (Ma et al, 2016;Tang et al, 2018). Due to drastic air pollution control in China since 2013, haze pollution has been controlled in recent years (the environmental statistics unit of a statistics center in Peking University, 2018), appearing as a sharp decrease in fine particulate matter.…”
Section: Introductionmentioning
confidence: 99%